Characterization and quantification of a CO2 and CH4 leakage experiment from a well into the carbonate vadose zone. (October 2018) - Rhino, Kévins; Loisy, Corinne; Cerepi, Adrian; Garcia, Bruno; Rouchon, Virgile; Khamlichi, Aïcha El; Noirez, Sonia
Highlights: An ultra diffusive leakage experiment was performed within a well at the subsurface of Saint Emilion pilot site. The gas phase of CO2, CH4, He and Kr was monitored and quantified in the vadose zone. Unlike the previous leakage experiments, the migration was mainly diffusive with no advective migration detected. CH4, He and Kr were used as different type of tracers for CO2 migration. The analysis of CO2 /He, CO2 /Kr and CO2 /CH4 ratios showed that the vadose zone acted as a buffering zone. Abstract: An ultra-diffusive leakage experiment was performed on the pilot site of Saint-Emilion near Bordeaux in France. It consisted in the injection of 85% CO2 and 5% of each He, Kr and CH4 in a vertical well with a very low injection pressure. This study allowed the development of an automated tool that continuously monitored the gas phase within the vadose zone. Measurements showed that the gas plume had a heterogeneous spatial and temporal variation. Mathematical calculations performed on the time series of the gas species showed that diffusive transport mainly occurred in the porous media. However, every stage of the migration could not be driven by diffusive process as shown by the exponential regression. A non-identified transport mechanism may have occurred during the increase of concentration. He was proven to be a suitable temporal tracer for a CO2 leakage as it was a good temporal precursor. Even if the process was weaker than in the former injection experiments, Kr could show help foreseeing the extent of the gas plume within the pilot site. CH4 was also shown to be an excellent temporal precursor of CO2 arrival. The amount of gas migrating through the preferential path identified in the previous experiment was weaker than in the previous study. Moreover, the monitoring showed that a significant amount of injected gas migrated deeper in the vadose zone. The ratios CO2 /Kr vs. CO2 /He and the evolution of CO2 /Kr, CO2 /He and CO2 /CH4 put in evidence three groups of probes. The first consists in the subsurface probes and is characterized by a potential reactive transport of CO2 through the vadose zone such as gas dissolution in the aqueous phase. The second group gathers the closest probes to the injection point and underlines a very slow return to baseline value through diffusion. The third group is characterized by a competition between the process occurring in the first and second group. Isotopic measurement of Kr could not bring relevant information about the CO2 fates into the vadose zone. However, it shows the possible presence of mechanism transport such as vertical flux and gravitational settlings. Observations from both of all the leakage experiment and future laboratory experiment could improve our understandings of the buffering zone and help to foresee CO2 leakage for future storage site.